Soft Copy versus Hard Copy Reading in Digital Mammography - Obenauer, Silvia (Springer-Verlag, 2004)
The objective of this study was to compare soft copy reading at a mammography work station with hard copy reading of full-field digital mammographic images. Mammograms of 60 patients (n = 29 malignant, n = 31 benign) performed with full-field digital mammography (Senographe 2000D, GE, Buc, France) were evaluated. Reading was performed based on hard copy prints (Scopix, Agfa, Leverkusen, Germany) and on 2 k × 2.5 k high-resolution monitors (Sun Ultra 60, Sun Microsystems, Palo Alto, California, USA). Four readers with different levels of experience in mammography categorized the mammograms according to the BI-RADS classification. The comparative study was performed by four readers, and at least 2 months elapsed between the reading sessions. Postprocessing, of course, was available only at the work station (windowing and leveling, zooming, inversion). Sensitivity, specificity, and positive predictive value were evaluated. Diagnostic accuracy of the evaluation was determined. Sensitivity for malignant lesions in hard copy versus soft copy reading was 97% vs 90%, 97% vs 97%, 93% vs 97%, and 76% vs 76% for the four readers, respectively. Specificity was 52% vs 68%, 58% vs 74%, 65% vs 48%, and 61% vs 68%. Accuracy for the classification of malignant lesions according to the BI-RADS categories showed no difference between hard copy and soft copy reading. Soft copy reading is possible with the available system and enables radiologists to use the advantages of a digital system.